Bahasa Inggris untuk Fakultas Dakwah & Ilmu Komunikasi (Tinjauan Umum Berdasarkan KKNI) - arwemi arwemi (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
English courses for Dakwah Faculty are MKDU (General and Basic Courses) courses or general courses that are not major subjects (non-major English). What figures and competencies will be given to students of this faculty? This article tries to explore the needs of English for FDIK (Dakwah and Communication Science Faculty) in general, and at a glance for each department in FDIK. There are several variations in the needs of graduates of each department on English. KPI (Islamic Broadcasting Communication) and MD (Dakwah Management) departments are more in speaking competence, BKI (Islamic Counseling) for reading comprehension, PMI (Islamic Social Development) department needs both, especially for interactions with international references and institutions